PENGARUH CITRA MEREK CONVENIENCE STORE TERHADAP REPUTASI DI MATA KONSUMEN SELAKU PELAJAR SMA KRISTOFORUS 2 (Studi Komparasi antara 7-ELEVEN dengan LAWSON’S STATION Cabang Palem, Jakarta Barat) - Rustono Farady Marta (Universitas Bunda Mulia, 2014)
Along the development era, in which human needs are no longer centered on SANDAG, food, and shelter, but it is rather the actualization needs and communication. In order to meet these needs, is now a place that has a convenience store concept started mushrooming in various parts of the world, especially in Indonesia. Two of the many convenience stores most visited Indonesian teenagers are 7-Eleven and Lawson's Station.This is a disturbing desire to continue the previous studies researchers entitled